Peran PKBM dalam Meningkatkan Akses dan Keberlanjutan Pendidikan Kesetaraan Paket C (Studi Kasus Pada PKBM MUMTAZ) - Abdul Hayyi; Padlurrahman Padlurrahman; Mohzana Mohzana; Badarudin Badarudin (JURNAL ASIMILASI PENDIDIKAN, 2026)
This study aims to analyze the role of PKBM Mumtaz in improving access to and sustainability of the Package C Equivalency Education Program for the community of Labuhan Haji Village, Labuhan Haji District, East Lombok Regency. The research focuses on: (1) the role of PKBM Mumtaz in improving access to Package C equivalency education; (2) the strategies and mechanisms employed in implementing the Package C program. This research employed a qualitative approach using a single-case study design. The research participants consisted of PKBM administrators, tutors, learners, community members, and local government representatives involved in the implementation of the Package C program. Data were collected through observation, in-depth interviews, and documentation. Data validity was ensured through source triangulation, technique triangulation, and time triangulation. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing and verification. The study concludes that PKBM Mumtaz plays a strategic role in expanding access to and ensuring the sustainability of Package C equivalency education through the provision of flexible, adaptive, and community-based educational services. The success of the program is supported by collaboration among administrators, tutors, learners, community members, and government institutions in promoting equitable educational opportunities for individuals who have limited access to formal education.